CRITICAL THINKING: A PRIMER FOR CHEMISTRY TEACHERS AND ACADEMICS - TIMOFTE, Roxana S. (Presa Universitară Clujeană, 2018)
The aim of writing this book was to offer a support to Chemistry teachers and academics in their endeavors to foster students’ critical thinking. The theoretical information was presented in an accessible way, while the focus was on offering models for learning objectives, class activities and evaluation methods.